(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
Digital transformation is conquering the world with a tremendous speed in every aspect of society and education is one important area. This fast advancement in technology is occurring in both the developed and developing societies. As a result, we see e-learning platforms extensively used and make the learning process continue in universities and education institutions almost uninterrupted, despite the restrictions of social interaction by governments during the covid-19 pandemic. The purpose of the study was to evaluate the User Acceptance and Adoption of the Digital Management Information System by focusing on E-Learning System in IDE at UNZA. The study was conducted on the students and lecturers who used the System at the IDE at UNZA. A google questionnaire was sent to the students in their groups and 271 participants answered the questionnaire successfully and this became the sample for the study. Data was analyzed using SPSS where the correlation and multi-variant Regression Analysis Model were used to help understand the data. The study found that the Social Influence (β= .657), was mostly significant in influencing User Acceptance Adoption of the System, seconded by Performance Expectancy ( and Effort Expectancy’s (. The study concludes that all the constructs are positively related to the acceptance and adoption of the E-Learning System. However, Social Influence is the most influenced factor User Acceptance Adoption of the E-Learning System at the University of Zambia when compared to the other constructs. This conclusion has added to the arguments which have found other factors like PE and EE to be factors affecting BI for the adoption of IT systems in other countries. The study recommended that the University of Zambia should link E- Learning system with the online library to assist student get the recommended resources. This can be done by adding a fee to facilitate which will help cater for the running costs while students and lecturers maximize the use of the system.